2021
DOI: 10.1021/jacs.0c12689
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Active Sites for High CO Selectivity during CO2 Hydrogenation over Supported Nickel Catalysts

Abstract: Controlling the selectivity of CO2 hydrogenation catalysts is a fundamental challenge. In this study, the selectivity of supported Ni catalysts prepared by the traditional impregnation method was found to change after a first CO2 hydrogenation reaction cycle from 100 to 800 °C. The usually high CH4 formation was suppressed leading to full selectivity toward CO. This behavior was also observed after the catalyst was treated under methane or propane atmospheres at elevated temperatures. In situ spectroscopic stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
5
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(130 citation statements)
references
References 68 publications
4
118
5
3
Order By: Relevance
“…As well, they are promising for CO 2 hydrogenation because of the dual-function of H 2 dissociation and C═O bond scission. [109][110][111][112] Porosoff et al 18 reported the CO 2 hydrogenation on defined Mo 2 C surfaces, which are highly active and selective for CO production. The Mo 2 C catalyst shows CO 2 conversion of 8.7% and CO/CH 4 ratio of 14.5 for CO 2 hydrogenation at 300 °C, which outperforms noble metal bimetallic catalysts.…”
Section: Carbide-based Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…As well, they are promising for CO 2 hydrogenation because of the dual-function of H 2 dissociation and C═O bond scission. [109][110][111][112] Porosoff et al 18 reported the CO 2 hydrogenation on defined Mo 2 C surfaces, which are highly active and selective for CO production. The Mo 2 C catalyst shows CO 2 conversion of 8.7% and CO/CH 4 ratio of 14.5 for CO 2 hydrogenation at 300 °C, which outperforms noble metal bimetallic catalysts.…”
Section: Carbide-based Catalystsmentioning
confidence: 99%
“…In addition to the Mo 2 C, other carbides such as Ni 3 C and InNi 3 C 0.5 were explored for CO 2 hydrogenation. 111,112 Although Ni is highly selective for methanation, both of Ni 3 C and InNi 3 C 0.5 with carbide structures exhibit superior RWGS feature. Chen et al 111 reported that the InNi 3 C 0.5 supported on Al 2 O 3 /Al-fiber shows over 97% CO selectivity in CO 2 hydrogenation under wide reaction conditions.…”
Section: Carbide-based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role played by nickel in CO 2 hydrogenation is well understood in terms of particle size [10] and metal-reactant intermediate reactions [19]. It has also been reported that oxygen vacancies in NiAl 2 O 4 promote the dissociation of CO 2 to CO [20] and facilitate the hydrogenation of adsorbed CO to atomic carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Catalysts such as Fe, Co, Ni and Cu supported on silica and carbon materials have been comprehensively investigated in CO2 hydrogenation. [78] Among them, Fe and Co-based catalysts are widely used in the CO2 modified FTS, due to the significant selectivity to C2+ hydrocarbons. [79] These active transition metal in the form of small nanoparticles or even clusters and single atom supported on metal oxides with large surface areas, such as γ-Al2O3, [80] ZrO2, [81] TiO2 [82] and CeO2 [83] have been frequently reported as solid catalysts for CO2 hydrogenation.…”
Section: Chapter 1 35mentioning
confidence: 99%